ANALYSIS OF MALAY PANTUN TRAINING BY USING PANTUN CARD GAME AS A MEDIA TO BUILD LOCAL WISDOM - Tengku Silvana Sinar; Syahron Lubis; Rohani Ganie (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2020)
This study aims to analyze a training held by the USU community service team in a program for the Implementation of Pantun Cards (Kartu Pantun) as a technique to train students at Madrasah Aliyah (MA) Sinar Serdang to create pantuns. There were two results of the training. Firstly, the training enriched the comprehensiveness of students’ insight on Malay culture especially in pantun creation. Secondly, through the simulation and role-play technique by using Pantun Cards, students and teachers activated their soft skill, especially in producing Malay Pantun. It can be concluded that the use of Pantun Cards and pictures as a teaching and training media has resulted on quite successful learning process. The implementation of simulation and role-play techniques by using Pantun Cards create a harmonious of teaching-learning situation and a strategic ways for the teachers and students to communicate and exchange pantuns.